The Effectiveness of Using Animated Films in Improving Students' Mastery of English Vocabulary - Zunia Adha Wati; Agus Setiawan; Umar Al-Faruq A Hasyim; Suhono, Suhono (CV. Creative Tugu Pena, 2025)
Vocabulary learning is a fundamental aspect of English language acquisition. However, many students still struggle to understand and retain new vocabulary. This study aims to examine the effectiveness of using animated films as a medium to enhance the vocabulary acquisition of eighth-grade students at MTs Nurul Falah. The research employed a quantitative method with a Time Series Design, where data were collected through pretests and posttests and analyzed using statistical tests. The research sample consisted of 45 students divided into two groups: the experimental group, which used animated films, and the control group, which used conventional teaching methods. The data analysis results showed a significant improvement in the posttest scores of the experimental group compared to the control group. The t-test produced a t-value of 6.85 with a significance level of 0.001 (<0.05), indicating that the use of animated films is effective in enhancing students' vocabulary acquisition. In addition, observational results indicated that students were more active, enthusiastic, and motivated during the learning process when animated films were used. This study supports the theory that visual-based media can enhance students' memory and understanding of learning materials. Therefore, the use of animated films can be recommended as an innovative teaching strategy for vocabulary learning in English.